Molecular role of the PAX5‐ETV6 oncoprotein in promoting B‐cell acute lymphoblastic leukemia. (20th February 2017) - Smeenk, Leonie; Fischer, Maria; Jurado, Sabine; Jaritz, Markus; Azaryan, Anna; Werner, Barbara; Roth, Mareike; Zuber, Johannes; Stanulla, Martin; den Boer, Monique L; Mullighan, Charles G; Strehl, Sabine; et al.
Abstract: PAX5 is a tumor suppressor in B‐ALL, while the role of PAX5 fusion proteins in B‐ALL development is largely unknown. Here, we studied the function of PAX5‐ETV6 and PAX5‐FOXP1 in mice expressing these proteins from the Pax5 locus. Both proteins arrested B‐lymphopoiesis at the pro‐B to pre‐B‐cell transition and, contrary to their proposed dominant‐negative role, did not interfere with the expression of most regulated Pax5 target genes. Pax5‐Etv6, but not Pax5‐Foxp1, cooperated with loss of the Cdkna2a/b tumor suppressors in promoting B‐ALL development. Regulated Pax5‐Etv6 target genes identified in these B‐ALLs encode proteins implicated in pre‐B‐cell receptor (BCR) signaling and migration/adhesion, which could contribute to the proliferation, survival, and tissue infiltration of leukemic B cells. Together with similar observations made in human PAX5‐ETV6 + B‐ALLs, these data identified PAX5‐ETV6 as a potent oncoprotein that drives B‐cell leukemia development. Synopsis: New mouse models for PAX5 fusion proteins found in acute lymphoblastic leukemia reveal that oncogenesis involves loss of cell cycle inhibitors rather than deregulation of known PAX5 target genes. Expression of the Pax5‐Etv6 fusion protein (as generated by recurrent translocations in human B‐ALLs) arrests B‐cell development at the pre‐BCR + stage in a Pax5 Etv6/+ mouse model. Pax5‐Etv6 functions as a potent oncoprotein that cooperates with loss of the tumor suppressor proteins Cdkn2a and Cdkn2b in the development of B‐cell acute lymphoblastic leukemia (B‐ALL). Pax5‐Etv6 regulates genes involved in cell adhesion and migration, which explains the broad tissue infiltration of Pax5 Etv6/+ Cdkn2ab +/− B‐ALLs. The likely cell of origin for B‐ALL development is the pre‐BCR + B cell, consistent with the Pax5‐Etv6‐dependent regulation of key genes involved in pre‐BCR signaling. Abstract : New mouse models for PAX5 fusion proteins found in acute lymphoblastic leukemia reveal that oncogenesis involves loss of cell cycle inhibitors rather than deregulation of known PAX5 target genes.